Simultaneous Determination of Haloperidol and Isopropamide Iodide in Pharmaceutical Dosage Forms by High Performance Liquid Chromatography-Diode Array Detection - Aziz Ramadan, Abdul; Mandil, Hasna; Lahmek, Mhammed (Asian Journal of Chemistry, 2011)
A specific, simple, sensitive and precise high performance liquid chromatography with diode array detection (HPLC-DAD) was developed for the assay of haloperidol and isopropamide iodide. Good chromatographic separation was achieved using a C18 (150 mm × 4.6 mm, 5 μm) column, mobile phase being methanol: phosphate buffer 50 mM (60:40 v/v) at pH 4.0 ± 0.2 and a flow rate of 1.5 mL/min. The peak was detected at 254 nm. The detector response were linear at concentrations over the range 10-1000 μg/mL and 2.0-1000 μg/mL for isopropamide iodide and haloperidol with percent relative standard deviation (RSD %) £ 4.8 and 4.1 %, respectively. The limits of quantification (LOQ) were at 3.67 and 0.018 μg/mL and the limits of detection (LOD) were at 1.21 and 0.0059 μg/mL for isopropamide iodide and haloperidol, respectively. The proposed method was successfully applied with high accuracy and good precision for the determination of isopropamide iodide and haloperidol in a various pharmaceutical formulations tablets with no interference from the excipients.